Pengaruh Customer Relationship Management dan Persepsi Harga terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan - Maghfira Rahmadilla Rahmadilla; Rivera Pantro Sukma (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
In facing increasingly complex challenges to maintain customer loyalty, the hotel industry must focus on effective strategies. This research focuses on the application of Customer Relationship Management (CRM) and price perceptions as a way to increase customer loyalty. CRM is considered a key strategy for creating additional value and building sustainable relationships with customers. The aim of this research is to analyze the influence of Customer Relationship Management and price perceptions on customer loyalty through customer satisfaction. This research involves customers with criteria of more than 1 visit. Data collection was carried out by distributing questionnaires to 150 respondents, using the purposive sampling method. Data analysis was carried out using SmartPLS 3.2 with structural Equation Modeling (SEM). The research results show that Customer Relationship Management has a significant effect on customer satisfaction, Customer Relationship Management has a significant effect on customer loyalty, price perception has a significant effect on customer satisfaction, price perception has a significant effect on customer loyalty, and customer satisfaction has a significant effect on customer loyalty.